Why We Should Promote Irrationality - Schmidt, Sebastian (Grazer Philosophische Studien, 2017)
The author defends the claim that there are cases in which we should promote irrationality by arguing (1) that it is sometimes better to be in an irrational state of mind, and (2) that we can often (purposefully) influence our state of mind via our actions. The first claim is supported by presenting cases of irrational belief and by countering a common line of argument associated with William K. Clifford, who defended the idea that having an irrational belief is always worse than having a rational one. In support of the second claim, the author then explains how the control we have over our beliefs could look like. In conclusion, the author suggests that the argument of this essay is not restricted to the irrationality of beliefs, but can be applied to irrational states of mind in general (like desires, intentions, emotions, or hopes). In an outlook on the “ethics of belief”debate, the author points out that the argument of this essay need not conflict with evidentialism, but does so when combined with another plausible claim about the meaning of doxastic ought-statements.
Keywords: rationality; reason; reasons; epistemic; belief; mind; control; mental state; normativity; ethics of belief; Clifford